Two new species of Sonerila Roxb. (Melastomataceae) from Laos - Phonepaseuth, Phongphayboun; Souladeth, Phetlasy; Souvannakhoummane, Keooudone; Vongthavone, Thyraphon; Tagane, Shuichiro (European Journal of Taxonomy, 2021)
Two new species of Sonerila Roxb. (Melastomataceae), S. erectifolia Phonep., Soulad. & Tagane sp. nov. from southern Laos, and S. souvannii Phonep. & Soulad. sp. nov. from central Laos, are described and illustrated. Comparisons with morphologically similar species are presented, along with ecological information and preliminary conservation status. A key to the species of Sonerila in Laos is also provided.